Another Look at the Sarima Modelling of the Number of Dengue Cases in Campinas, State of Sao Paulo, Brazil - Etuk, Ette Harrison; Ojekudo, Nathaniel (International Journal of Natural Sciences Research, 2014)
Martinez, et al. [1] analysed monthly numbers of dengue cases as reported in Campinas, southeast Brazil from 1998 to 2008, by SARIMA methods. Assuming X is the original series, they analysed the logarithm of X + 1. The models they proposed and compared are of orders (2,1,2)x(1,1,1)12, (2,1,1)x(1,1,1)12, (1,1,2)x(1,1,1)12, (1,1,1)x(1,1,1)12, (2,1,3)x(1,1,1)12, and (1,1,3)x(1,1,1)12. Using the R software, they chose the SARIMA(2,1,2)x(1,1,1)12 model as the best on the basis of Akaike information criterion, AIC. The result in this work is different: the SARIMA(2,1,1)x(1,1,1)12 model is herein adjudged as the best on the same minimum AIC grounds.